An improvement of passenger service charge collection system for Malaysia Airports Berhad / Siti Aniza Hasan - Hasan, Siti Aniza (1995)
Passenger service charge or the airport tax that is levied on departing Passenger, is one of the MAB's greatest income. However, this income can be increased by making a profit through these collections. As for the present collecting system, the profit is earned more by Airline companies, who is responsible for collecting PSC on behalf of the Airport authority. The options to replace the practised system will be identified based on the criteria that give advantages to MAB and passengers. These systems will be selected by carrying out the alternative procedures in evaluation of Alternatives. The selected alternative is based on the collection of PSC directly from Passengers by the airport authority. Therefore, no through ticket or coupon Will be practised anymore.